Novel Epstein-Barr virus immunoglobulin G–based approach for the specific detection of nasopharyngeal carcinoma. - Abdulamir, Ahmed Sahib; Hafidh, Rand Riadh; Abu Bakar, Fatimah; Abbas, Kassim Ali (Elsevier, 2010)
Purpose This study was designed to find a reliable Epstein-Barr virus (EBV) immunoglobulin (Ig) G–based diagnostic/screening test for nasopharyngeal carcinoma (NPC) able to demarcate between the NPC-related seropositivity of EBV IgG antibodies and that of other head and neck cancer (HNCA) and control groups. The NPC-associated immunosuppression affects EBV IgA much more than IgG, leading to inconsistent detection of NPC using EBV IgA antibodies.